Efikasi diri dan penyesuaian diri siswa baru Sekolah Menengah Atas - Soleh, Ahmad Ivandi; Permadi, Dimas Agil (PSYCOMEDIA : Jurnal Psikologi, 2024)
Adaptation of new students is a process experienced by students in facing rapid and constant environmental changes, and the students need an adaptation process to undergo it. Self-efficacy is an individual's belief in his or her ability to achieve results in certain situations and conditions. This research aims to determine the relationship between self-efficacy and adjustment in new students. The research sample consisted of 150 students. The research results show that there is a significant relationship between self-efficacy and adjustment in new high school students. The higher the self-efficacy, the better the adjustment ability of new high school-level students.